A bottom-to-up drainage and water pressure reduction system for railway tunnels. (November 2018) - Li, Pengfei; Liu, Hongchuan; Zhao, Yong; Li, Zheng
Abstract: Due to the high water pressure at the bottom of the tunnel, when drainage system is not well designed, railway ballast bed may suffer from diseases such as contamination, mud pumping, excessive settlement and so on. Poor drainage will significantly reduce the performance and durability of ballast bed. In this paper, a novel conceptual drainage and water pressure reduction system at the bottom of railway tunnel is proposed. The proposed bottom drainage system includes a transverse catchment system, a longitudinal water conducting system and a bottom-to-up water drainage system. A series numerical analyses were carried out to validate the performance of the proposed drainage system. Results show that the proposed drainage and pressure reduction system can effectively discharge the water at the bottom of the railway tunnel and reduce the water pressure. Factors that influence the performance of the proposed drainage system are also discussed by parametric studies. The permeability of the surrounding rock, the initial support and the secondary lining invert have great influences on the external water pressure. The groundwater level that influences the water pressure reduction effect are also discussed.